The scope of university work in intercultural universities in Perú - Solís-Castillo, Julio César (2021)
The purpose of this article is to address the work of intercultural universities of our country, as a response and solution to strengthen uses, habits, customs, native language and identity in the educational process of young indigenous students, in order to train multicultural citizens and bilingual professionals